Generation of high-quality GeV-class electron beams utilizing attosecond ionization injection. (7th April 2021) - Lécz, Zsolt; Andreev, Alexander; Kamperidis, Christos; Hafz, Nasr
Abstract: Acceleration of electrons in laser-driven plasma wakefields has been extended up to the 10 GeV energy within a distance of 10s of centimeters. However, in applications, requiring small energy spread within the electron bunch, only a small portion of the bunch can be used and often the low-energy electrons represent undesired background in the spectrum. We present a compact and tunable scheme providing clean and mono-energetic electron bunches with less than one percent energy spread and with central energy on the GeV level. It is a two-step process consisting of ionization injection with attosecond pulses and acceleration in a capillary plasma wave-guide. Semi-analytical theory and particle-in-cell simulations are used to accurately model the injection and acceleration steps.